Assessing maintenance contracts when preventive maintenance is outsourced - Wu, Shaomin (Elsevier Science B.V., Amsterdam., 2012)
In some companies, corrective maintenance is conducted in-house but preventive maintenance might be outsourced. This raises a need to optimise some parameters such as the number of contracts from a perspective of the equipment owner. This paper considers a maintenance policy for such a situation, analyses the roles of the parameters in a PM model, proposes approaches to defining bonus functions, and finally discusses special cases of both the PM policy and the bonus function. Numerical examples are also given to explore the impact of parameters on the expected lifecycle cost rate.